2006
DOI: 10.1007/s00423-005-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

The sentinel node biopsy in early gastric cancer: a preliminary study

Abstract: The detection rate of this procedure was 100%. The preliminary results and perspectives for feasibility of sentinel node biopsy and its accuracy in predicting the nodal status in early gastric cancer are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Finally, 46 feasibility studies involving 2,684 patients were enrolled in this meta‐analysis. The details of these 46 studies are provided in Table I 18–63.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 46 feasibility studies involving 2,684 patients were enrolled in this meta‐analysis. The details of these 46 studies are provided in Table I 18–63.…”
Section: Resultsmentioning
confidence: 99%
“…A disadvantage of laparoscopic SN biopsy, however, is its invasiveness. Although studies on laparoscopic SN biopsy have shown its potential [76][77][78][79], various technical and material limitations still have to be overcome. Also, the reliability of laparoscopic SN biopsy has yet to be determined by multicenter prospective clinical trials [80].…”
Section: Discussionmentioning
confidence: 99%
“…First, the general preference to visualize SLNs has shifted toward a double-tracer (dye plus isotope) method. [32][33][34]36,40,44,47,52 Many researchers have reported substantial improvement by the combined use of both techniques in the rate of identification of SLNs, [32][33][34]47,53,58 although some authors did not agree with that idea. 40 Hayashi et al 10 stated that a reduction in the SR would result if either the dye-guided or radioguided method was used solely.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Ishizaki et al 30 Prospective Park et al 31 Prospective comparison Lee et al 32 Prospective Mura et al 33 Prospective Saikawa et al 34 Prospective 2007…”
Section: Identification Of Slnsmentioning
confidence: 99%
See 1 more Smart Citation